2012
DOI: 10.1111/j.1744-7917.2012.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Moth diversity in three biofuel crops and native prairie in Illinois

Abstract: The expanding demand for biofuel feedstock may lead to large-scale conscription of land for monoculture production of biofuel crops with concomitant substantial negative impacts on biodiversity. We compared moth diversity in light-trap samples from corn, miscanthus, switchgrass and native prairie, to determine whether there is an observable relationship between plant species diversity and moth abundance and diversity. Moth alpha diversity was highest in prairie and was higher in switchgrass than in the other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Zangerl et al (45), for example, contrasted arthropod detritivore communities in native prairie, switchgrass, and miscanthus systems and found surprisingly few differences in detritivore community structure or function. Lepidopteran alpha (within-field) diversity, in contrast, was greatest in native prairie (2.9 species per trap night, on average), intermediate in switchgrass (2.4 species), and lower in miscanthus and corn (1.8 species) (46). Gardiner et al (47) quantified insect pollinator and predator communities in fields of corn, switchgrass, and restored prairie in Michigan and Wisconsin; they found that although the numbers of bee species were similar, individual species were more abundant in switchgrass and prairie than in corn by a factor of 3 to 4.…”
Section: Biodiversity Benefits Can Extend To Nearby Croplandmentioning
confidence: 89%
“…Zangerl et al (45), for example, contrasted arthropod detritivore communities in native prairie, switchgrass, and miscanthus systems and found surprisingly few differences in detritivore community structure or function. Lepidopteran alpha (within-field) diversity, in contrast, was greatest in native prairie (2.9 species per trap night, on average), intermediate in switchgrass (2.4 species), and lower in miscanthus and corn (1.8 species) (46). Gardiner et al (47) quantified insect pollinator and predator communities in fields of corn, switchgrass, and restored prairie in Michigan and Wisconsin; they found that although the numbers of bee species were similar, individual species were more abundant in switchgrass and prairie than in corn by a factor of 3 to 4.…”
Section: Biodiversity Benefits Can Extend To Nearby Croplandmentioning
confidence: 89%
“…Many butterfly species are threatened worldwide, mainly as a consequence of habitat destruction (Bonelli et al ., ), and that many more will probably become threatened in the near future if current ecological trends continue (Balletto et al ., ; Settele et al ., ). Moreover it has been demonstrated that the intensive cultivation of oilseed rape decreases Lepidoteran biodiversity (in this case moths) both in the fields and the surrounding landscape (Harrison & Berenbaum, ).…”
Section: Discussionmentioning
confidence: 99%
“…Its host species are several Brassicaceae, including S. arvensis and B. oleracea . In addition, we have to remember that many other non‐target organisms can be phytophagous on Brassicaceae (Chifflet et al ., ; Harrison & Berenbaum, ; Mesa et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Brin et al 2012; Danielsen et al 2009;Dhondt et al 2004;Fry and Slater 2011;Rowe et al 2011). Findings show that bioenergy impacts depend on the type of bioenergy (Harrison and Berenbaum 2012;Haughton et al 2009;Myers et al 2012;Questad et al 2011;Robertson et al 2011aRobertson et al , 2012Werling et al 2011), management activities (Myers et al 2012), reference habitat (Felten and Emmerling 2011;Questad et al 2011) and landscape structure Robertson et al 2011bRobertson et al , 2013; Fig. 1).…”
Section: Linking Empirical Studies With Modelling Studiesmentioning
confidence: 94%